Peran Destination Attributes dalam Meningkatkan Revisit Intention: Kasus pada Turis di Keraton Ngayogyakarta Hadiningrat - Alsa Yuda Putri; Usep Suhud; Rahmi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study examines to analyze destination attribute effects on revisit intention at Keraton Ngayogyakarta Hadiningrat. The study focuses on variables of destination attributes, destination reputation, tourist satisfaction, and memorable tourism experiences. Data collection was conducted through a survey using a questionnaire as the instrument. The study involved 250 respondents who were residents of DKI Jakarta or DI Yogyakarta and had visited Keraton Ngayogyakarta. The collected data were analyzed using SPSS and SEM in AMOS to manage the data and analyze the research findings. The results of this study, based on its hypotheses, indicate that the hypothesis of destination attributes' influence on destination reputation is accepted and significant. Similarly, the hypothesis of destination attributes' impact on tourist satisfaction is accepted and significant, as well as the hypothesis of destination attributes' effect on memorable tourism experiences. Moreover, the hypothesis of destination reputation's influence on revisit intention is accepted and significant, along with the hypothesis of tourist satisfaction's impact on revisit intention and the hypothesis of memorable tourism experiences' effect on revisit intention